Dabigatran versus Warfarin for acute venous thromboembolism in elderly or impaired renal function patients: pooled analysis of RE-COVER and RE-COVER II - Goldhaber, Samuel Zachary; Feuring, Martin (Thrombosis and haemostasis, 2017)
Management of acute venous thromboembolism (VTE) with anticoagulants in elderly patients and those with chronic kidney disease poses special challenges. The RE-COVER and RE-COVER II trials showed that dabigatran 150 mg twice daily was as effective as warfarin over 6 months in preventing recurrent VTE, with a lower bleeding risk. We now assess the effects of old age and renal impairment (RI) on pooled trial outcomes in 5,107 patients: 4,504 aged <75 years and 603 aged ≥75 years. The primary efficacy outcome was symptomatic VTE/VTE-related death. Safety outcomes were centrally adjudicated major bleeding events (MBEs), MBEs or clinically relevant non-major bleeding events (MBEs/CRBEs) and any bleeds. Baseline renal function was categorized as normal, mild RI or moderate RI. A total of 3,698 had normal renal function and 1,100 and 237 had mild and moderate RI, respectively (23 patients with severe RI and 49 with missing creatinine clearance data were not included). For dabigatran, VTE/VTE-related death decreased from 3.1% (normal renal function) to 1.9% for mild RI and to 0.0% for moderate RI. For warfarin, the event rates were 2.6, 1.6 and 4.1%, respectively. Overall, major bleeding increased with increasing RI (p = 0.0037) and with age (p = 0.4350), with no apparent difference between the dabigatran and warfarin patients. Dabigatran shows better efficacy than warfarin in RI and in the elderly patients, probably because of an increase in the concentration of dabigatran. However, bleeding risk increases with both dabigatran and warfarin in the presence of RI.